(untitled) (Comparatismi, 2024)
The aim of the essay is to analyse the chronotopic motif of the party in some canonical texts of British Modernism: Joyce’s The Dead (1914), Mansfield’s The Garden Party (1922), Woolf ’s Mrs Dalloway (1925) and To the Lighthouse (1927). Although the home protects intimacy from unwelcome intrusions, the party transforms it into a liminal space where inside and outside, private and public interact: the external world with its turmoil enters the domestic space and the private dimension of the party, spoiling the festive mood, which may or may not successfully contain the intrusion. Frequently the intruder from the outside takes on the aspect of a deceased person, who challenges the principles of the individual and the society where they belong. Though Joyce’s, Mansfield’s and Woolf’s narratives are set in a domestic space scantly described if compared to 19th century novels, places are nonetheless constantly evoked as the plot unfolds aptly foregrounding the final revelation and the ultimate meaning of the text.